2018
DOI: 10.1111/psj.12276
|View full text |Cite
|
Sign up to set email alerts
|

Fearing Food: The Influence of Risk Perceptions on Public Preferences for Uniform and Centralized Risk Regulation

Abstract: Public opinion features prominently in policy research because it sets bounds on the definition of policy problems and acceptable policy solutions. We contend that public opinion is also important for setting bounds on the level of government at which policy hazards are regulated by shaping preferences for uniformity of regulation and, relatedly, preferences for centralization. We offer a theoretical argument for why risk creates pressures for uniform standards and examine the extent to which preferences for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
1
14
2
Order By: Relevance
“…As previously stated, both issue causality and issue image, elements of problem definition, have positive and significant relationships with individual policy support for both state and federal government. However, when we examine problem definition in an explicitly comparative manner, the significant relationship for issue image becomes null, seen in Figure below, in contrast to the findings of Maestas et al's () study of food regulation.…”
Section: Resultscontrasting
confidence: 61%
See 3 more Smart Citations
“…As previously stated, both issue causality and issue image, elements of problem definition, have positive and significant relationships with individual policy support for both state and federal government. However, when we examine problem definition in an explicitly comparative manner, the significant relationship for issue image becomes null, seen in Figure below, in contrast to the findings of Maestas et al's () study of food regulation.…”
Section: Resultscontrasting
confidence: 61%
“…These studies primarily operationalize issue images as risk perceptions, where issues are first perceived on a scale which ranges from extremely low or no risk to extremely high risk. These studies have found that high‐risk perceptions are associated with changes in individuals' behaviors and lead to more support for government mitigation policies (Leiserowitz, ; Maestas, Chattopadhyay, Leland, & Piatak, ; Martin, Martin, & Kent, ; O'Connor, Bard, & Fisher, ). Furthermore, numerous studies have demonstrated the effect of issue causality on individual policy choice.…”
Section: Problem Definition and Policy Choice At The Individual Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike previous research published in this journal (e.g., see Beyer & Hänni, 2018; Burstein, 2020), these articles move away from attempting to answer the age‐old question of whether public opinion influences policy, instead analyzing perception formation as well as individual experiences of policy outcomes. Maestas, Chattopadhyay, Leland, and Piatak (2020) examine the influence of risk perceptions on policy preference formation by drawing distinctions between preferences for uniformity and centralization in regulation. The authors argue that this distinction is important for federalism, namely because an essential emotional component of risk perception (e.g., anxiety or worry) is likely to motivate the public to seek uniformity in regulation as well as a centralized venue for policy issues that transcend state boundaries.…”
mentioning
confidence: 99%